Analysis Of Students' Mathematical Problem-Solving Difficulties Assembled From Learning Styles Using The Problem-Based Learning Model Using Geogebra - Niken Adelina Silalahi; Hamidah Nasution; Mangaratua M Simanjorang (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2026)
This study aims to analyze students' mathematical problem-solving difficulties in terms of learning styles using the GeoGebra-assisted problem-based learning model. This study uses a descriptive qualitative approach. The subjects of the study consisted of 32 eighth-grade students grouped based on learning styles, namely accommodation, divergent, assimilation, and convergent. Data collection techniques were carried out through learning style questionnaires, mathematical problem-solving ability tests, and interviews. Data analysis was carried out through data reduction, data presentation, and drawing conclusions based on difficulty indicators, namely difficulties in facts, concepts, principles, and operations, which were associated with the stages of Polya's problem-solving. Based on the results of the study of 32 students, it was found that students with an accommodation learning style numbered 7 students (21.87%), a divergent learning style numbered 11 students (34.37%), an assimilation learning style numbered 9 students (28.12%), and a convergent learning style numbered 5 students (15.62%). From the results of interviews with students, for the accommodation of learning style, they experienced difficulties in the concept, principle, and operation indicators. Students with a divergent learning approach experience difficulties with indicators of concepts, principles, and operations. Students with an assimilation learning style experience difficulties with indicators of facts, principles, and operations. Students with a convergent learning style experience difficulties with indicators of principles and operations.